The Role of Epithelial and Vascular-Endothelial Cadherin in the Differentiation and Maintance of Tissue Integrity - Petr Nachtigal; Andrea Gojová; Vladimír Semecký (Acta Medica, 2001)
The present review has focused on the cell adhesion molecules from the cadherin superfamily, in particular on E- and VE-cadherin. In general, cadherins are a large group of cell adhesion molecules located at intercellular junctions called adherent junctions. They play an important role in embryogenesis and morphogenesis in animals and humans due to their adhesive and cell-signalling functions. Disturbances of the expression or function of cadherins and their associated proteins called catenins are crucial for the initiation and development of many pathological states. E-cadherin is an epithelium-specific cadherin that is required for the development and maintenance of the normal function of all epithelial cells in tissues. The loss or down-regulation of E-cadherin is a key event in the process of tumour invasion and metastasis. The assessment of E-cadherin immunoreactivity may be a useful prognostic marker in some cancers, complementary to the established prognostic factors. VE-cadherin is an endothelium-specific cadherin, which plays a relevant role in vascular homeostasis. It has been demonstrated that VE-cadherin is required for normal vasculogenesis, angiogenesis, and for the maintenance of vascular integrity. Disruption of VE-cadherin-catenin complexes by some inflammatory agents such as thrombin, by inflammatory cells, or shear stress is accompanied by an increase in vascular permeability in vivo and in vitro.